Two novel acervus species extend their distribution within Yunnan, China - Anusha H. Ekanayaka (2018)
© 2016 Magnolia Press. Acervus is a small genus in Pyronemataceae. Most of the species in this genus have been recorded from China. In the present study, two species of Acervus from Yunnan Province, in southwestern China, were investigated by using morphology and DNA sequence data. This paper introduces two new species A. stipitatus and A. globulosus, with morphological descriptions, and compares them with morphologically similar taxa. Multi-gene phylogenetic analyses inferred from 28S, TEF1 and RPB2 sequence data strongly support the lineages for taxa of Acervus, corresponding to morphological features. We also provide a summarized comparison of the important morphological characteristics of Acervus species.